Female Indigenous entrepreneurship in remote communities in northern Australia - L., Cecil A. (Information Management and Business Review, 2014)
Little is known about Australian Indigenous female entrepreneurship. Misconceptions typifying Australian Indigenous businesses are community enterprises are encumbered by research limitations, generalisations and stereotyping; the material is seldom voiced by Australian Indigenous people; and few sources detail the challenges for grass roots female Indigenous entrepreneurs in remote Australian Aboriginal communities that maintain patriarchal cultures. In this paper is described how 21 Indigenous female entrepreneurs in a remote region of northern Australia have tailored their businesses to comply with the regulatory and statutory framework of the dominant society while preserving sensitivity to the traditional cultural norms, rules, and obligations. The data were independently corroborated by Indigenous and non Indigenous men of recognised standing in the region. These empirical observations provide foundation for better informed judgements about the business environment in remote regions of Australia, which is fundamental when developing policies for delivering sustainable female Indigenous small businesses.